Inovasi Peningkatan Keterampilan Berbicara Bahasa Arab di Gontor Putri - Putri, Syifa Firdausi; Rahman, Nurul Insani; Anggraini, Reyka Mei (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
Pondok Modern Darussalam Gontor, which is approaching its centennial, has succeeded in creating a generation that has Arabic language skills, especially speaking skills. One of the productive language skills is speaking, which is the person's ability to produce language orally. To achieve these skills, Pondok Modern Darussalam Gontor Putri 1 carries out innovative language activities. Apart from being an institutional identity, Arabic is also a language of communication and a language of instruction in the learning process. The research aims to describe the activities carried out at Gontor for Girls 1st Campus as an innovation in improving the Arabic speaking skills. This research uses qualitative. Researchers employ direct observation and interviews with students and teachers as data collection methods. The data analysis used in this research is Miles and Huberman. The results of this research is, that Pondok Modern  Darussalam Gontor based on the Kulliyatul Mu'allimati-l-Islamiyyah curriculum, learning speaking skills is delivered intracurricularly and extracurricularly. Learning in the classroom, which is mostly in Arabic and delivered using direct methods carried out by the teacher, is a form of intracurricular activity. Meanwhile, extracurricular activities as innovations to support improving students' Arabic speaking skills are muhadatsah shobahiyah, speech practice, idhof lughowiy, haditsu-l-itsnain, art performances, and Arabic super camp.